Atomic structure and dynamics of single platinum atom interactions with monolayer MoS2 - Li, H; Wang, S; Sawada, H; Han, G; Samuels, T; Allen, C; Kirkland, A; Grossman, J; Warner, J (American Chemical Society, 2017)
We have studied atomic level interactions between single Pt atoms and the surface of monolayer MoS2 using aberration-corrected annular dark field scanning transmission electron microscopy at an accelerating voltage of 60 kV. Strong contrast from single Pt atoms on the atomically resolved monolayer MoS2 lattice enables their exact position to be determined with respect to the MoS2 lattice, revealing stable binding sites. In regions of MoS2 free from surface contamination, the Pt atoms are localized in S vacancy sites and exhibit dynamic hopping to nearby vacancy sites driven by the energy supplied by the electron beam. However, in areas of MoS2 contaminated with carbon surface layers, the Pt atoms appear at various positions with respect to the underlying MoS2 lattice, including on top of Mo and in off-axis positions. These variations are due to the Pt bonding with the surrounding amorphous carbon layer, which disrupts the intrinsic Pt-MoS2 interactions, leading to more varied positions. Density functional theory (DFT) calculations reveal that Pt atoms on the surface of MoS2 have a small barrier for migration and are stabilized when bound to either a single or double sulfur vacancies. DFT calculations have been used to understand how the catalytic activity of the MoS2 basal plane for hydrogen evolution reaction is influenced by Pt dopants by variation of the hydrogen adsorption free energy. This strong dependence of catalytic effect on interfacial configurations is shown to be common for a series of dopants, which may provide a means to create and optimize reaction centers.